O tempo da memória em Viagem ao Egito, Jordânia e Israel, de Pedro Nava - Gabriel, Maria Alice Ribeiro (2022)
The main objective of this doctoral thesis is to analyse Viagem ao Egito, Jordânia e Israel (1998), a fragmente of the notebooks or diaries of the Brazilian doctor and writer Pedro da Silva Nava, considering references to Jewish culture and history in his diary, Memoirs and historical essays. Notably after World War II, there were scholarly works written in several fields of knowledge, such as the historiography, social sciences, literary and cultural studies that took as their object of analysis the representation of Jews in literature. In the post-war period, Jewish authors who narrated their experiences gave new impetus to the autobiographical genre. Autobiographies, biographies and memoirs combines aspects of fiction, historiography or journalism to report the past. These writings presented original representations of the Jewish people, different of the stereotypes recorded and transmitted by the literature, politics, popular culture and religion. By representing facts with resources from the historian and the ficction writer, the memoirist offers an authentic and differentiated perspective of the past. Based on this assumption, this research is justified by the lack os studies so far on this travel diary and by the panoramic portrait of Israel delimited in the work by the author. Pedro da Silva Nava (1903-1984), doctor and rheumatology professor, is one of the most important Brazilian’s authors of the twentieth century due to his collection of Memoirs: Baú de Ossos (1972), Balão Cativo (1973), Chão de Ferro (1976), Beira-Mar (1978), Galo-das-trevas (1981), O Círio Perfeito (1983) e Cera das Almas (2006). This collection brings representative portraits of Brazilian culture and society in the nineteent century and early twenties. Influenced by Marcel Proust, Pedro Nava created biographical portraits depicting personal characteristics of people and groups by analogies to artistical, historical and literary personages. He published articles in the field of rheumatogy research, dedicated essays to the history of medicine, disease, health sciences, and their relation to society. Although Pedro Nava was not a professional historian, his essays on social history of medicine have real merit, constituting an extensive and recorrent topic in his Memoirs. He stated that years of professional experience as physician sharpened his sense of observation and shaped his literary writing. He was interest in genelogy and issues concerning to the future of personal and family archives, which assume a determinant function in his Memoirs. Pedro Nava examined archives, documents, genealogies and bibliographical sources; colected reminiscences; transcribed oral and written reports; made caricatures and drawings to compose biographical profiles. In order to discuss the authir’s travel notes in Viagem ao Egito, Jordânia e Israel, this research takes a comparative approach of historical- literary content, considering studies on diary writing and the memorialistic genre.